Alzheimer's disease-associated inflammatory pathways might contribute to osteoporosis through the interaction between PROK2 and CSF3 - Zhang, Wenzheng; Zhang, Ya; Hu, Naixia; Wang, Anying (Frontiers in Neurology, 2022)
This study aimed to explore the potential molecular pathways and targets of Alzheimer's disease leading to osteoporosis using bioinformatics tools. The Alzheimer's and osteoporosis microarray gene expression data were retrieved from the Gene Expression Omnibus, and differentially expressed genes in the blood microenvironment related to Alzheimer's disease and osteoporosis were identified. The intersection of the three datasets (GSE97760, GSE168813, and GSE62402) was used to obtain 21 co-expressed targets in the peripheral blood samples in patients with Alzheimer's disease and osteoporosis. Based on the degree algorithm, the top 10 potential core target genes related to these diseases were identified, which included CLEC4D, PROK2, SIGLEC7, PDGFB, PTCRA, ECH1, etc. Two differentially expressed mRNAs, Prokineticin 2 (PROK2) and three colony-stimulating factor 3 (CSF3), were screened in the GSE62402 dataset associated with osteoporosis. Protein–protein rigid docking with ZDOCK revealed that PROK2 and CSF3 could form a stable protein docking model. The interaction of PROK2 and CSF3, core genes related to osteoporosis inflammation, plays an important role in the mechanism of osteoporosis in patients with Alzheimer's. Therefore, abnormalities or alterations in the inflammatory pathways in the peripheral blood samples of Alzheimer's patients may affect the course of osteoporosis.